2023
DOI: 10.3390/ijms24021352
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Energy Metabolism in the Regulation of Thermogenic Brown Fats and Human Metabolic Diseases

Abstract: Brown fats specialize in thermogenesis by increasing the utilization of circulating blood glucose and fatty acids. Emerging evidence suggests that brown adipose tissue (BAT) prevents the incidence of obesity-associated metabolic diseases and several types of cancers in humans. Mitochondrial energy metabolism in brown/beige adipocytes regulates both uncoupling protein 1 (UCP1)-dependent and -independent thermogenesis for cold adaptation and the utilization of excess nutrients and energy. Many studies on the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 246 publications
1
9
0
Order By: Relevance
“…This is further supported by the observation that continuous treatment with Ang II decreased the phosphorylation of HSL and CREB as downstream events in the cAMP signalling pathway (Supplementary Fig. S7 B) 41 . However, transient treatment with Ang II enhanced the phosphorylation of CREB, but not of HSL.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…This is further supported by the observation that continuous treatment with Ang II decreased the phosphorylation of HSL and CREB as downstream events in the cAMP signalling pathway (Supplementary Fig. S7 B) 41 . However, transient treatment with Ang II enhanced the phosphorylation of CREB, but not of HSL.…”
Section: Discussionsupporting
confidence: 60%
“…Our study also found that the Ang II-activated mitochondrial energy status led to the repression of UCP1 transcription, similar to the feedback regulation described above. These results may partially explain the obesity-associated repression of UCP1 expression under the hyperactivation of the RAS during obesity 19 , 41 .
Figure 7 A schematic illustration of Ang II effects on metabolic reprogramming and mitochondrial energy metabolism in ciBAs.
…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The mitochondrial metabolism (mitochondrial energy metabolism, and UCP1 expression/activity) in BAT tissues is also impaired by obesity, as reported in clinical and preclinical studies [ 73 , 74 ].…”
Section: Obesity and Mitochondrial Metabolism In Wat And Batmentioning
confidence: 96%